Isolasi dan Pengujian Aktivitas Penghambat Enzim Alfa Glukosidase dari Bakteri Endofit Daun Kumis Kucing (Orthosiphon aristatus (Blume) Miq.) - Indah Tamara Herman Putri; Rustini; Friardi Ismed; Valdy F Sardi; Nurwahidatul Arifah (Postgraduate, University of Mataram, 2024)
Orthosiphon aristatus (Blume) Miq., commonly known as kumis kucing, is frequently used in traditional Indonesian medicine to treat diabetes, hypertension, rheumatism, gout, and as a diuretic. However, large-scale production of medicinal products from natural sources requires significant raw material and land, creating a need for alternative methods. This study explores the potential of isolating endophytic bacteria from kumis kucing leaves to serve as α-glucosidase enzyme inhibitors, offering a more sustainable approach. Eight bacterial endophytes were isolated and tested using bioautography assays and IC50 measurements to assess their inhibitory activity. Four isolates—KK 1, KK 3, KK 4, and KK 5—demonstrated significant α-glucosidase inhibition, with IC50 values of 41.35 µg/mL, 57.04 µg/mL, 56.70 µg/mL, and 164.16 µg/mL, respectively. Molecular testing identified KK 1 as Priestia aryabhattai, while KK 3 and KK 5 were identified as Priestia megaterium. These findings suggest that endophytic bacteria isolated from Orthosiphon aristatus leaves have the potential to be developed as natural sources of α-glucosidase inhibitors, which are beneficial for diabetes management.